Physical working capacity and maximal steady state of heart rate - Eduardo Rumenig; Fábio Yuzo Nakamura; Maria Augusta Pedutti Dal'Molin Kiss; Rômulo Cássio de Moraes Bertuzzi (Universidade Federal de Santa Catarina, 2010)
The objectives of this study were to determine whether the power output measured by physical working capacity at threshold heart rate (PWCTHR) was equivalent to power output at the maximal steady state of heart rate (MSSHR), and to analyze the infuence of exercise duration on the calculation of PWCTHR. Seven subjects were submitted to a maximal progressive test and five bouts at constant power relative to the second metabolic threshold (Lim2). Heart rate (HR) and HR variability were estimated by linear regression and Poincaré plotting, respectively. There was a signifcant difference between PWCTHR and MSSHR, irrespective of the intensity used. Additionally, intensities higher than 50% of Lim2 did not result in HR stabilization. However, the latter fnding did not depend on cardiovascular autonomic control since there was no difference in SD1 or SD1/SD2 as a function of duration of the effort. Thus, PWCTHR does not represent MSSHR in physically active young adults. Furthermore, the lack of HR stabilization seems to be independent of neural mechanisms.